An improved coupled inductor‐based quadratic step‐up DC–DC converter with a high step‐up factor and reduced voltage overshoot on the power switch - Mahnaz Izadi; Ali Mosallanejad; Alireza Lahooti Eshkevari (IET Power Electronics, 2024)
Abstract Most coupled inductor‐based step‐up DC–DC converters encounter a significant voltage overshoot on their power switch due to the leakage inductance of the coupled inductor. So, they need additional bulky snubber circuits or a sophisticated procedure for coupled inductor design to reduce that effect. This paper proposes an improved coupled inductor‐based DC–DC converter, which provides a high quadratic voltage conversion ratio without excessive voltage stresses on the power switch. An active clamp circuit that operates with the zero‐voltage switching (ZVS) feature has been utilized for this aim. This feature allows the main power switch to be selected from low voltage ratings and low on‐resistance MOSFETs, which reduces conduction loss. The topology also benefits from continuous input current, high gain, high efficiency, and an appropriate number of components compared with the produced gain. In this article, the theory and operation of this converter are described by proposing the dc and small‐signal models, loss model, and continuous and discontinuous current modes (CCM and DCM) relations. Experimental results are represented to evaluate the performance of the proposed topology. For this purpose, a 240 V/240 W prototype has been designed and fabricated. Results confirm the above claims.